If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -8x = -110x + 6x Combine like terms: -110x + 6x = -104x -10 + -8x = -104x Solving -10 + -8x = -104x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '104x' to each side of the equation. -10 + -8x + 104x = -104x + 104x Combine like terms: -8x + 104x = 96x -10 + 96x = -104x + 104x Combine like terms: -104x + 104x = 0 -10 + 96x = 0 Add '10' to each side of the equation. -10 + 10 + 96x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 96x = 0 + 10 96x = 0 + 10 Combine like terms: 0 + 10 = 10 96x = 10 Divide each side by '96'. x = 0.1041666667 Simplifying x = 0.1041666667
| 1/3*2/7 | | 4n+3m=12 | | .3x+6=7.5 | | 6(K-86)=36 | | 39+x-9*3=25 | | 37=7d-26 | | 4.5(x+2.4)=-13.5 | | 1/7x-8=-3 | | 21+7h=91 | | 9x+3(5x+y)=15 | | 1/3*7/8 | | 88=8(b+2) | | 15x-10=5(2x-7) | | 4z-4=8 | | (8-5)+2x+(3x-10)=180 | | 4a+3=2x | | 13=4t+5 | | 3(p+6)(p+5)=0 | | 5x-2x=4 | | 4p=4p-12 | | -2/5(x-4)=-2 | | 0.5y-0.1(y+3)=0.2(2y+1)-0.7 | | 10+3d=19 | | 13-2m=7 | | 1/2*2/8 | | 0.5y-0.1(y+3)=0.2 | | 4m-23=-27+5m | | y-52/6=5 | | b^0=0 | | b^0=1 | | 8b+12=92 | | 1/2y-7/2=-1/3y-5 |